การสกัดดีบุกออกจากฮาร์ดเฮดโดยการย่างแร่แบบออกไซด์และหลอมกับโซเดียมไฮดรอกไซด์ - จุฑาลักษณ์ บุญนาคค้า (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
In this research work, the extraction of tin from tin - iron alloy or hardhead which is the product obtained during tin smelting was investigated. The hardhead containing 32.40 %Sn and 45.81 %Fe was ground to different sizes and oxidized at 500 to 800°C for 1 to 6 hours to form SnO2 and Fe2O3. The results indicated that an increase in oxidation temperature decreased the oxidation time. However, too high oxidation temperature (800°C) resulted in sintering of the oxide particle obtained In sodium hydroxide fusion stage, effects of fusion temperature, fusion time, the amount of NaOH and oxide particle sizes on tin leaching were investigated. When the oxide particle of -400+500 mesh size was fused with 750% excess of NaOH at 700°C for 2 hours it was found that 96.66% tin in the form of Na2SnO3 could be extracted by hot water (60°C) while the iron oxide remained in residues.